Volume Tables for Trees in Home Gardens of Kerala - Krishnankutty, C. N. (Indian Forester, 2013)
Teak (Tectona grandis Linn.), jack (Artocarpus heterophyllus Lamk.), anjily (A. hirsutus Lamk.), matty (Ailanthus triphysa Dennst.) and mango (Mangifera indica Linn.) trees are commercially and economically important tree species in home gardens of Kerala. Different types of volume prediction equations were developed for each species through regression analysis, using data on diameter (m3) at breast-height level (1.37 m from ground) of sample trees before felling and corresponding volume (m3) of commercial timber measured after felling. Volume of a tree refers to that under-bark of logs or billets with mid-girth (over-bark) 40 cm and above, in the case of teak, matty and mango trees. It refers to that under-sapwood (volume after removing sapwood) of logs with mid-girth (over-bark) 60 cm and above, in the case of jack and anjily trees. Using the best fitted equation selected from the set of 27 equations estimated for each species, volume estimates were predicted for those values of diameter corresponding to the values of girth at breast-height from 60 cm upwards with an interval of 5 cm. By tabulating the girth in cm and volume in m, volume tables were prepared for each species. The tables provide volume estimates corresponding to different values of girth at breastheight of trees which can easily be measured at site. The tables are useful to tree growers and purchasers, for obtaining an estimate of volume in a tree by referring the tables without felling the tree.